2009
DOI: 10.1097/gme.0b013e3181a6b491
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, urinary incontinence, and female sexual dysfunction

Abstract: Increased BMI early in menopause represents a risk both for UI and for sexual dysfunction. Weight control has an essential role in postmenopause and should be considered early in perimenopause to safeguard female quality of life as well as to prevent or improve UI and female sexual dysfunction symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 43 publications
1
16
2
2
Order By: Relevance
“…Our results were consistent with those of Kolotkin et al (6). Other studies have shown a significant relationship between sexual function and BMI (1,8,28). The differences in the findings concerning whether high BMI correlates with sexual dysfunction may due to variations in research methods in the sexual function field, diverse study backgrounds, and finally, differences among participants.…”
Section: Discussionsupporting
confidence: 83%
“…Our results were consistent with those of Kolotkin et al (6). Other studies have shown a significant relationship between sexual function and BMI (1,8,28). The differences in the findings concerning whether high BMI correlates with sexual dysfunction may due to variations in research methods in the sexual function field, diverse study backgrounds, and finally, differences among participants.…”
Section: Discussionsupporting
confidence: 83%
“…Consequently, further research is needed to assess to what extent postoperative changes in related variables including body image and health-related quality of life [18, 20, 21, 24, 25], reproductive hormones [26], and endocrine and metabolic parameters [6, 10, 27] may account for these improvements, and whether there is a minimum weight loss requirement for improvement in sexual functioning. Additionally, depression and drugs used in its treatment are frequently associated with FSD [23, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Aging is known to be the most important risk factor for female UI, affecting menopausal women, with indices of 43% in the 35 to 81 year age group17 ) . A number of urinary disorders can be caused by decreased bladder capacity in women with more than 10 years since menopause onset compared to those with less than 5 years, decreasing from between 500 and 600 ml to between 250 and 300 ml after menopause.…”
Section: Discussionmentioning
confidence: 99%